1987
DOI: 10.1093/oxfordjournals.eurheartj.a062172
|View full text |Cite
|
Sign up to set email alerts
|

Left bundle branch block: prevalence, incidence, follow-up and outcome

Abstract: In a randomly selected population screening study of 8450 men and 9039 women 33 to 71 years of age conducted in Iceland in 1967-1977, 27 men and 17 women were found to have left bundle branch bock (LBBB). The prevalence of LBBB at that time was 0.43% for men and 0.28% for women. The incidence of LBBB was 3.2 per 10,000 per year for men and 3.7 per 10,000 per year for women. All except one of 37 alive patients with LBBB were examined in 1984 including chest X-ray, echocardiography and exercise testing (Bruce pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
2
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(49 citation statements)
references
References 1 publication
3
42
2
2
Order By: Relevance
“…Conduction delay leads to abnormal ventricular depolarization and disturbance of the synchrony between interand intraventricular contraction and relaxation (Hardarson et al 1987;Grines et al 1989;Xiao et al 1992;Fahy et al 1996;Nelson et al 2000;Saxon et al 2000). Disturbance of ventricular synchrony causes a shortening in diastolic filling and effective ejection time, reduces stroke volume, prolongs mitral regurgitation and leads to an increase in global and regional wall stress (Grines et al 1989;Xiao et al 1992;Nelson et al 2000).…”
mentioning
confidence: 99%
“…Conduction delay leads to abnormal ventricular depolarization and disturbance of the synchrony between interand intraventricular contraction and relaxation (Hardarson et al 1987;Grines et al 1989;Xiao et al 1992;Fahy et al 1996;Nelson et al 2000;Saxon et al 2000). Disturbance of ventricular synchrony causes a shortening in diastolic filling and effective ejection time, reduces stroke volume, prolongs mitral regurgitation and leads to an increase in global and regional wall stress (Grines et al 1989;Xiao et al 1992;Nelson et al 2000).…”
mentioning
confidence: 99%
“…13 In the Reykjavik studies, no increased death rate due to coronary artery disease or hypertension was observed among people with left bundle-branch block. 14 In people Ͻ60 years old with right bundle-branch block, there was a positive correlation to hypertension. 15 Several studies have found increased mortality in patients with bundle-branch block and concomitant cardiovascular disease.…”
mentioning
confidence: 99%
“…The relationship of LBB with dilated left ventricle and systolic dysfunction may be explained by impaired myocardial conduction. The occurrence of LBB was associated with increasing left ventricular dimensions and decreasing left ventricular fractional shortening in epidemiological studies (11,12).…”
Section: Discussionmentioning
confidence: 91%